Multiple causal pathways of high-quality development for semiconductor enterprises in China - Shichuan Li; Xinjie Yang (PLoS ONE, 2026)
As China’s economy undergoes transformation, enhancing the high-quality development of semiconductor enterprises has profound implications for overall economic growth. This study constructs a multi-factor configurational model influencing the high-quality development of semiconductor enterprises based on the Technology-Organization-Environment framework and conducts configurational analysis using the fuzzy-set qualitative comparative analysis method. The results indicate that high-quality development is a systematic process where no single factor is a necessary condition for the high-quality development of semiconductor enterprises. Five paths lead to high-quality development, which can be categorized into three types: innovation capability and enterprise size-dominated type, innovation capability and human capital level-driven type, and multi-factor linkage type. The study investigates the mechanisms of high-quality development from a structural perspective, providing insights into the synergistic effects of various factors and revealing the complex relationships underlying high-quality development.